PENERAPAN MODEL QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS IVB SD NEGERI 106 PEKANBARU - Puji Wahyuni Puji Wahyuni; Gustimal Witri Gustimal Witri; Hamizi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT. This research is motivated by the low value of math. Preliminary data result of learning students of class IVB of 106 elementary school Pekanbaru is from the 30 students, only 13 peoples or 43,44% completed or reached the KKM and 17 peoples or 56,67% were not completed. Based on these problems, it is necessary given way to solve the problem include applying Quantum Teaching model. Quantum Teaching give an opportunity for students to learn with a pleasant atmosphere and engaging students to increase math studies. Data collection instrument on this research are observation sheet activities of teacher and student, and learning outcomes. Subjects in this research were students of class IVB of 106 elementary school Pekanbaru. This research was conducted in three cycles, by doing the daily test of the end of each cycle. The result of this research shows that the Quantum Teaching model can increase math studies, completeness math learning outcomes in first cycle is 66,67%, in second cycle increased to 93,33% and reach 100% in third cycle.Keywords : Quantum Teaching Models, Mathematics Learning Outcomes